The citizenship in the training of High School students in the dimension of teaching methodologies (Research, Society and Development, 2021)
The present study aimed at analyzing the unfolding of citizenship in the training of high school students in the dimension of teaching methodologies and teaching itself. It is characterized as qualitative descriptive and interpretative. Two high schools were selected, one is public (school A) and the other is private (school B), both located in a city in Vale dos Sinos/RS, Brasil. For data collection, we used the document analysis (PPP), observations, field journals and interviews with the directive team and teachers, through snowball sampling. We realized that in school A, the connections, contextualization, criticism and reflections are more limited due to the traditional method of teaching. Therefore, the formation of citizenship constitutes itself through the framing of social behavior and in the preparation for work. In school B, the active and collaborative methods foster the training of discerning, reflective and more autonomous students.